Effects of the closed fishing season on small-scale fisheries and coastal livelihoods in Ghana - Victor Owusu (Fisheries and Aquatic Sciences)
The main aim of fisheries management is to achieve sustainability of the resource. This paper investigates the potential of closed fishing season as an effective conservation measure in increasing fish stocks in Ghana. The study contributes empirically to the literature on fisheries governance and marine conservation challenges in Sub-Saharan Africa using a political ecology approach. The study utilized a mixed-methods approach, which consisted of 300 household surveys and 40 interviews with major stakeholders. The study’s findings revealed no significant increase in fish production since 2016, after implementing the closed season in Ghana. The seasonal closures have further impoverished fisherfolk livelihoods through low fish catch and income. These findings suggest that implementing the temporal fishing bans alone without other management interventions would not yield positive ecological and economic outcomes. Therefore, fisheries managers must collaborate with fisherfolk, the coastal communities, NGOs, and other concerned stakeholders to achieve sustainable management of fisheries resources. The study recommends stringent enforcement of the rules and regulations concerning illegal fishing activities and the introduction of social intervention programs to ameliorate the economic hardship of fisherfolk during the closed season.